Degradation of contaminants in plasma technology: An overview - Sanito, Raynard Christianson; You, Sheng-Jie; Wang, Ya-Fen (Journal of hazardous materials, 2022)
The information of plasma technologies applications for environmental clean-up on treating and degrading metals, metalloids, dyes, biomass, antibiotics, pesticides, volatile organic compounds (VOCs), bacteria, virus and fungi is compiled and organized in the review article. Different reactor configurations of plasma technology have been applied for reactive species generation, responsible for the pollutants removal, hydrogen and methane production and microorganism inactivation. Therefore, in this review article, the reactive species from discharge plasma are presented here to provide the insight into the environmental applications. The combinations of plasma technology with flux agent and photocatalytic are also given in this review paper associated with the setup of the plasma system on the removal process of metals, VOCs, and microorganisms. Furthermore, the potential of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) inactivation via plasma technology is also described in this review paper. Detailed information of plasma parameter configuration is given to support the influence of the critical process in the plasma system to deal with contaminants. [Display omitted] •Different types of plasma technology system have been used widely in many research fields.•Plasma bubble reactor shows a good result on the treatment of organic pollutants.•Many reactive species play an integral role to degrade pollutants in the plasma system.•SARS-CoV-2 virus can be inactivated via an atmospheric-cold plasma.